120 ARPEGGIO OP. 1 MAURO GIULIANI: PENGARUHNYA TERHADAP KUALITAS PETIKAN GITAR KLASIK - SUPRIANDO, SUPRIANDO (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
Abstract120 Arpeggio Op. 1 developed by Mauro Giuliani is a technique exercises specifically targeting the improvement of the ability of the right finger for classical guitarists. Various variations or complete right finger exercise formulas are summarized in 120 Arpeggio Op. 1 Mauro Giuliani. This research was conducted with the aim to find out about any aspect of the right hand that had improved after practicing using the 120 Arpeggio Op. 1 technique exercises method of Mauro Giuliani. The results of this research showed that there were several things that technically the right hand had improved after doing the exercises with the M. Giulian method, including: (1) Speed of the plucking, (2) Finger synchronization when plucking the string, (3) Accuracy of the finger when plucking the guitar strings and (4) Articulation. The method used in this study is a qualitative method by prioritizing explanations which are then forwarded analytically to the research object.